Celiac disease and headache in children: a narrative state of the art: Celiac disease and headache - Sabino, Luca; Marino, Silvia; Falsaperla, Raffaele; Pisani, Francesco; Massimino, Carmen; Pavone, Piero (Acta Biomedica Atenei Parmensis, 2020)
Celiac disease (CD) is one of the most important entity of the wide spectrum of gluten-related disorders (GRDs). It is well known that neurological manifestation can be present either at the onset of CD, or appear during the development of the pathology, and different can be the neurologic findings. Clinical features are very variable, ranging from typical manifestations of gastrointestinal involvement to neurologic symptom. The most frequent neurologic signs reported were headache, epileptic seizure, migraine, mental retardation, ataxia and attention deficit and hyperactive disorder. Headache either in form of migraine, or in non-specific form represents one of the main clinical presentation in CD. The aim of this work is to provide a narrative review of the pediatric literature focused on the cephalalgic features of children with CD evaluating the potential benefits of a gluten free diet (GFD). Papers were identified by searching for related literature in Medline (PubMed) and Embase using the words “Celiac Disease” and “Headache” or “Migraine” by specifying “children”/“paediatric age” for reports published since 1972 till 31th October 2018. According to our inclusion criteria, a total of 25 papers has been evaluated. Although it is still controversial if headache is prevalent in CD children a correct compliance to a GFD seems to improve the neurological symptoms even if the underlying pathogenic relationship between CD and neurologic system involvement is still not fully understood.